ANALYSIS OF EFFICIENCY IN LIQUID SEAL WITH THE USE OF MECHANICAL SEAL - Estambasse, Eduardo Costa [UNESP]; Ferreira, Flavio Antunes [UNESP]; Anjos, Marco Antonio dos [UNESP]; Bronieira, Paulo; Nunes, Willian R. B. M.; Leite, Evandro de Souza; Foschini, Cesar Renato [UNESP]; Gomes, JFS; Meguid, S. A. (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2016)
Sealing systems plays an important role in the industry, the study of the components of these systems evaluates and predicts the life of equipment working under harsh regimes. This paper proposes the development of a bench where you can collect various types of data and results. Can be evaluated in this device the sealing system for mechanical seals and gaskets. An interchangeable flange of the replacement condition of parts of seal. The drive is done by an alternating current motor, which can be variable rotation proposal for data collection. It will be constructed a mathematical model in order to equalize product loss and component wear.
Keywords: Seals; mechanical seals; gaskets